REVIEW ARTICLE: AMEBIASIS MOLECULAR PATHOGENESIS DEVELOPMENT - Muliani, Nurlina; Salim, Hotimah Masdan (UNUSA Press, 2019)
Amebiasis is one of the gastrointestinal tract infection disease caused by Entamoeba histolytica ,a parasitic protozoan. Amebiasis is the second disease, caused by parasite, that leading cause of death after malaria. Infection occurs through faecal-oral route and after ingestion a contaminated food and beverages by human faeces. The pathogenesis of E. histolytica can be classified into 3 processes, i.e: death of host cell, inflammation, and parasitic invasion. The recent years, a molecularly amebiasis pathogenesis has been developed, i.e: adherence, phagocytosis, tropogocytosis of host cell and how the parasites can survive and attack host cells so it can cause an infection in humans. Molecular development is an important thing to be considered in the selection of amebiasis therapy.